The Relationship Between Fear of Failure and Academic Procrastination in Elders Who Are Working on Thesis - Fabiola Ester Karunia Pangalila; Doddy Hendro Wibowo (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
Students come from various family backgrounds, individuals who are born as the eldest child will face various demands in living their lives so that they are prone to experiencing feelings of insecurity, anxiety or worry when facing failure, this condition has an impact on individuals, namely by the emergence of procrastination behavior. The purpose of this study was to determine the relationship between fear of failure and academic procrastination in the eldest child who is a student working on a thesis in North Sulawesi. This study used an incidental sampling technique involving 105 participants. Data collection uses a scale of fear of failure and academic procrastination. The results showed that the value of Rxy = 0.154 and sig. = 0.058 had a positive relationship between fear of failure and academic procrastination